Characterization and Anti-Inflammatory Potential of an Exopolysaccharide from Submerged Mycelial Culture of Schizophyllum commune - Du, Bin; Yang, Yuedong; Bian, Zhaoxiang; Xu, Baojun (Frontiers in Pharmacology, 2017)
Background and Purpose: Mushroom polysaccharides have attracted attention in food and pharmacology fields because of their many biological activities. The structure characterization and anti-inflammatory activity of exopolysaccharide from Schizophyllum commune were evaluated in present study. Methods: An exopolysaccharide from a submerged mycelial fermentation of Schizophyllum commune was obtained using DEAE-52 cellulose and Sephadex G-150 chromatography. The molecular weight (MW), monosaccharide compositions, chemical compositions, methylation analysis, circular dichroism studies, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectra, scanning electron microscopy, and atomic force microscopy were investigated. Results: It was a homogeneous protein-bound heteropolysaccharide with MW of 2900 kDa. The exopolysaccharide contained a β-(1→3) glycosidic backbone, (1→4)- and (1→6)- glycosidic side chain, and high amount of glucose. The anti-inflammatory activity of exopolysaccharide was assessed by inhibiting the production of nitric oxide (NO), inducible nitric oxide synthase (iNOS), and 5- lipoxygenase (5-LOX) from macrophages. This exopolysaccharide significantly (p < 0.05) inhibited lipopolysaccharides-induced iNOS expression levels in the cells in a dose-dependent manner. Conclusion: It indicated significant anti-inflammatory effects, which showed that exopolysaccharide might be exploited as an effective anti-inflammatory agent for application in NO-related disorders such as inflammation and cancer.